Synthesis of Zeolitic Macrocycles Using Site-Selective Condensation of Regioselectively Difunctionalized Cubic Siloxanes - Saito, Shohei; Wada, Hiroaki; Shimojima, Atsushi; Kuroda, Kazuyuki (Inorganic chemistry, 2018)
The designed synthesis of inorganic cyclic compounds is a significant topic because of their many potential applications. In this study, we used a building block approach to synthesize siloxane-based macrocycles that resemble zeolite apertures. We synthesized a regioselectively functionalized cubic octasiloxane having two adjacent corners modified with Si–O–C bonds via the reaction of octa(hydridosilsesquioxane) (H8Si8O12) with 2,2′-(o-phenylenedioxy)diethanol. Hydrolysis and condensation of the Si–O–C bonds yield the cyclic compounds consisting of three, four, and five cage siloxane units. These compounds have more rigid ring structures than conventional cyclic organosiloxanes. Such an approach will lead to the design of a new class of host materials and molecular channels for transport and separation.